Early Maladjustment Schemas in Individuals with and without Type 2 Diabetes Mellitus - Fazlolah Mirdrikvand; Mohammad Ali Sepahvandi; Siamak Khodarahimi; Simin Gholamrezaei; Mojtaba Rahmian Bougar; Pejman Shafikhani (Journal of Mind and Medical Sciences, 2019)
Objective. This study explored Early Maladjustment Schemas (EMSs) among individuals with and without type 2 diabetes mellitus and examined potential moderating roles for gender, level of education, and occupation. Methods. The sample included 371 adult participants (120 patients with diabetes and 251 individuals without diabetes), from Shiraz City, Fars province; Iran. The Young Schema Questionnaire-Short Form (YSQ-SF) was used to assess early maladjustment schemas. Results. Findings showed that patients with type 2 diabetes had significantly higher scores than controls on a number of EMSs, including abandonment, failure, vulnerability, enmeshment, self-sacrifice, entitlement, and insufficient self-control schemas as well as the over-vigilance and inhibition schematic domains. However, results did not support roles for gender, the level of education, and occupation on any of EMSs and schematic domains. Conclusions. Medical and health professionals may find these results helpful for assessment, treatment, and prevention goals in patients with type 2 diabetes.